Securing Cloud Data by Using Multi Keyword Search System - A, Prasannakumar Reddy; M, Vikram; N, Sudhakar Reddy (International Journal of Computer Sciences and Engineering, 2019)
Securing Cloud data is a major task in current ongoing world. Now a days Cloud playing a major role in every technical aspect, for data storage. Here secure data management in Cloud is the major challenge to achieve. Attribute based encryption (ABE) is the most commonly used algorithm for circulated registering, where a data provider redistributes the data that is encoded, to a cloud master association, and can grant the data to customers having express accreditations (or qualities). Regardless, the standard ABE structure doesn’t reinforce secure Deduplication, the basic rule for discarding multiple copies of undefined data to save additional room and framework information move limit. Here a trademark based limit structure is presented with checked duplication in a cream cloud setting, where a private cloud is responsible for duplicate disclosure and an open cloud manages the limit. Differentiating the previous systems which support data deduplication, our structure has bi-ideal conditions. Generally it might be used in a rapid manner to secretly give data to customers by choosing access plans as opposed to sharing translating keys. However, it is very helpful in acquiring the thought of semantic security which follows standard mechanism for data protection while the previous mechanism just simply achieved it by describing a flimsier security thought. Also, we put forward a framework to change a figure message more than one access system into figure works of the identical plaintext yet under various access courses of action without revealing the major plaintext.